Effect of spirulina sp. In combination with inorganic or organic fertilizers on growth and yield of okra (abelmoschus esculentus l) - Rumana, K.H.; Jeyakumar, K.; Gnanavelrajah, N.; Kirisan, A. (Proceedings of the 10th YSF Symposium - 2022, 2022)
Organic agriculture has emerged as a major focus field globally nowadays. The usage of chemical fertilizers alone has several adverse effects on the environment and human wellbeing, in addition, they must be replenished on a regular basis [1]. Organic fertilizers have been shown to improve soil fertility and increase soil biodiversity. Spirulina Sp.extract contains nutrients, sugar, and amino acids, as well as growth-promoting bioregulators, vitamins, amino acids, and other secondary metabolites, all of which support plant growth, hence it has also been recommended as a good protein source in animal feeds as well as an excellent alternative to chemical fertilizers [2]. Cattle manure (CM) application to the farmland has been a long-term practice in crop production worldwide. However, the application of cattle manure alone would demand bulk application due to its low nitrogen content. In addition, due to the present pandemic situation, inorganic fertilizer (IN) supply is limited and there is uncertainty of future supply. On this background two experiments were aimed, the first, to find the effect of Spirulina Sp. in combination with CM or IN except nitrogen (INEN) on nutrient availability in soil through a laboratory incubation study. The second experiment was to assess their effect on growth and yield of Okra (Abelmoschus esculentus L) local variety in a net house pot experiment study